2022
DOI: 10.1007/s00417-021-05530-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography (OCT-A) in retinitis pigmentosa and macular dystrophy patients: a retrospective study

Abstract: Purpose To evaluate macular vascular abnormalities in patients with macular dystrophies (MD) and retinitis pigmentosa (RP) through application of optical coherence tomography angiography (OCT-A). Methods In this retrospective study, patients with MD and RP were examined by OCT-A and compared to healthy individuals. OCT-A images were analyzed regarding the diameter and surface area of the foveal avascular zone (FAZ) as well as flow (FL) in different retinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The mean follow-up ranged between 2 months and 36 months [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Overall, significant reductions in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were observed in all the affected patients of the evaluated cohorts over time [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In addition, all the studies that explored the involvement of choriocapillaris (CC) demonstrated its significant impairment in RP patients [12,[15][16][17][21][22][23]25,…”
Section: Oct-a In Retinitis Pigmentosamentioning
confidence: 99%
See 1 more Smart Citation
“…The mean follow-up ranged between 2 months and 36 months [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Overall, significant reductions in both the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were observed in all the affected patients of the evaluated cohorts over time [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In addition, all the studies that explored the involvement of choriocapillaris (CC) demonstrated its significant impairment in RP patients [12,[15][16][17][21][22][23]25,…”
Section: Oct-a In Retinitis Pigmentosamentioning
confidence: 99%
“…In addition, all the studies that explored the involvement of choriocapillaris (CC) demonstrated its significant impairment in RP patients [12,[15][16][17][21][22][23]25,30,31]. Several authors focused on the variation of the foveal avascular zone (FAZ) area in RP patients, two-thirds of which described an increased avascular area [12,15,19,20,26,31], while the remaining third demonstrated its significant reduction [16,17,29]. Nakajima et al and Alnawaiseh et al explored an interesting association between the reduction in optic nerve head (ONH) vessel density (VD) in RP patients and the deterioration of the visual field mean deviation (MD) [15,27].…”
Section: Oct-a In Retinitis Pigmentosamentioning
confidence: 99%